Exploring the binding mechanism of saccharin and sodium saccharin to promoter of human p53 gene by theoretical and experimental methods. Issue 2 (22nd January 2020) - Mansourian, Mahboubeh; Mahnam, Karim; Rajabi, Hamid Reza; Roushani, Mahmoud; Doustimotlagh, Amir Hossein
Abstract: In the past few decades, extensive discussions have been on the impact of artificial sweeteners on the risk of cancer. The present study aimed to evaluate the interaction of saccharin (SA) and sodium saccharin (SSA) with the promoter of the human p53 gene. The binding ability was assessed using the spectroscopic technique, molecular docking and molecular dynamics (MD) simulation methods. Free energy of binding has been calculated using Molecular Mechanics/Poisson–Boltzmann Surface Area (MM/PBSA) method. Fluorescence spectra of mentioned gene with concentration profiles of SA and SSA were obtained in a physiological condition. A gradual increase without any significant spectral shift in the fluorescence intensity of around 350 nm was evident, indicating the presence of an interaction between both compounds and gene. The docking results showed that both compounds were susceptible to bind to 5′-DG56DG57-3′ nucleotide sequence of gene. Furthermore, the MD simulation demonstrated that the binding positions for SA and SSA were 5′-A1T3T4-3′ and 5′-G44T45-3′ sequences of gene, respectively. The binding of these sweeteners to gene made significant conformational changes to the DNA structure. Hydrogen and hydrophobic interactions are the major forces in complexes stability. Through the groove binding mode, the non-interactive DNA-binding nature of SSA and SA has been demonstrated by the results of spectrofluorometric and molecular modeling. This study could provide valuable insight into the binding mechanism of SA and its salt with p53 gene promoter as macromolecule at the molecular level in atomistic details. This work can contribute to the possibility of the potential hazard of carcinogenicity of this sweetener and to design and apply new and safer artificial sweeteners. Abbreviations: SA Saccharin SSA Sodium Saccharin Pp53g promoter of human p53 gene MD Molecular dynamics RMSD Root-mean-square deviation RMSF Root-mean-square fluctuation Rg Radius of Gyration SASA Solvent-Accessible Surface Area ADI Acceptable daily intake MM/PBSA Molecular Mechanics/Poisson–Boltzmann Surface Area Communicated by Ramaswamy H. Sarma